Rancang Bangun STEIN sebagai Media Pembelajaran Diagnosis Kerusakan Sistem Kelistrikan pada SMK Bidang Keahlian Teknik Otomotif - Wayan, Dodik (BRILIANT: Jurnal Riset dan Konseptual, 2024)
Electrical is an important part of the vehicle system. It is important for Automobile Technology students to master electrical systems. The electrical system learning currently available is still in the form of a trainer board which is intended for getting to know components, understanding basic circuits, and assembling electrical systems. However, this learning media cannot stimulate students to work according to SOPs and think critically. One solution to maximize media trainers is STEIN. STEIN (Smart with Trouble - Arduino Android) is an electrical learning medium that aims to give students experience in diagnosing damage to complex electrical systems. This media was developed using the ADDIE development model. The advantage of STEIN is that it is an open source technology product that has received a positive response from students and teachers.